Borderland Situation and Periferality in the North-Eastern Part of the Great Hungarian Plain - Baranyi, Béla; Balcsók, István; Dancs, László; Mező, Barna (Discussion Papers, 1999)
The study of the questions of borders and borderlands, the separating and connecting role of political state borders has special importance nowadays, especially regarding the current European integration processes. Spatial-ethnic problems of the past make the European co-operation and integration more difficult along the borders of the Central-Eastern European countries, particularly in the post-socialist countries like Hungary. The borders where unsettled socio-economic-ethnic questions accumulate and still exist mean considerable obstacles to globalisation and integration tendencies. The borderlands and settlements of North-Eastern Hungary - “peripheries of the periphery” - can be considered such a problematic territory. These extended borderlands comprise the most typical features of the especially disadvantageous peripheries. Finally it is important to note that the research completed in the North-Eastern Great Plain borderlands - considering all the choices and advantages, success and failure connected to the new task - means only the first and initial step of this kind of studies. Carrying on the research on the transformation and choices of all the Great Plain borderlands, the complete and detailed analysis of the borderlands gaining crucial importance after the EU accession would be possible in a few years. The analysis would contain the different possibilities of the peripheries and questions like the shaping gate and mediator role, the cross-border territorial integration relations and the ethnic and societal relations. Without too much self-conceit, it can be stated that the yet incomplete studies that have already been carried out in the North-Eastern Great Plain borderlands may secure a sufficient basis for the continuation and success of such a current issue.